2011
DOI: 10.1007/s12011-011-9154-2
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Selenite-Induced Apoptosis Mediated by ROS Attack in Human Osteosarcoma U2OS Cells

Abstract: Sodium selenite (Na(2)SeO(3), SSE) is an inorganic Se compound that is widely used in cancer chemoprevention studies. SSE has been shown to have anti-proliferative effects on several types of human cancer cells, but its effect on osteosarcoma cells has thus far not been reported. In this study, the cytotoxic effect of SSE on osteosarcoma cells U2OS was investigated in vitro and found to be higher than on comparable non-cancer cell lines 293 and L6. Treatment with SSE decreased cell growth in a dose- and time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 19 publications
3
37
0
Order By: Relevance
“…This is consistent with the earlier findings that ROS generation could induce osteosarcoma destruction. 34 …”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the earlier findings that ROS generation could induce osteosarcoma destruction. 34 …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that selenium can inhibit cell proliferation, inducing injury via generation of reactive oxygen species (ROS) (Rudolf et al, 2008). ROS levels can activate the JNK pathway and caspases-3 and 9 via cytochrome c, with down-regulation of Bcl-2 and up-regulation of Bax (Chen et al, 2012). Also, it has been demonstrated that (C 6 H 5 Se) and (4-ClC 6 H 4 Se) 2 present higher thiol peroxidase activity and an improved antioxidant potential than (3-CF 3 C 6 H 4 Se) and (4-MeOC 6 H 4 Se) in vivo (Meotti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…c and DNA fragmentation. Other organic and inorganic selenium compounds have been shown to induce caspase-mediated apoptosis, including MeSeCys, selenite (Suzuki et al, 2010), sodium selenite (Chen et al, 2012), and selenium dioxide (SeO 2 ) (Rikiishi, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SSE-triggered apoptosis correlated with the activation of CASP 3, downregulation of Bcl-2, and upregulation of P53, and PTEN in U2OS cells. Thus, the studies state that SSE is a promising anticancer compound that would be used in future therapies for OS [38].…”
Section: 7dihydroxy3'4'6trimethoxymentioning
confidence: 99%